Development of Character Education Model Based on The Four Pillars - Nur Irsyadiah; Marhamah; Farhana (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
The condition of Indonesia today is far from the expected ideal, because of the rampant corruption, environmental destruction, deviation, dishonesty, and behavior that violates various rules that seem to have become a habit. Education becomes a serious concern for the wider community when morality is marginalized in the system of behaving and behaving in society. As a result, on the one hand, the education that has been carried out has made humans more intellectually educated. However, on the other hand, the education that is carried out makes humans lose their humanity. Life and education are like a parallel electrical scheme. Both are related to each other. The implication is that if society wants a prosperous life, the content and process of education must be directed at meeting these needs. Thus, education should be able to bring changes in life in a more civilized direction. Various approaches to development in karate continue to be carried out, one of which is through content writing which will develop character education based on four pillars. This study uses a qualitative method with a research and development approach. The purpose of this study was to determine the implementation of the development of a four-pillar-based character education model.